If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2s-12s=4s-12
We simplify the equation to the form, which is simple to understand
2s-12s=4s-12
We move all terms containing s to the left and all other terms to the right.
+2s-12s-4s=-12
We simplify left and right side of the equation.
-14s=-12
We divide both sides of the equation by -14 to get s.
s=0.857142857143
| 2s-122s=4s-12 | | 3x-25=2x+4 | | 4f+3f+18=11 | | 4x+6(x+2)=33 | | 11x-201=2x-12 | | 13-10x=98-45x | | 6n+13=46 | | 2.3x+3.9-6.62x=0.12 | | 4x+9=-15x-8 | | 0.01x^2+0.006x-0.08=0 | | x=-2/3+4 | | 49x^2+90x-22=0 | | c=15.57m | | 7ab*4ab= | | 6/2(1+2)=a | | 34.1/(-5.5)= | | 34.1(-5.5)= | | 26+(17x)=-42 | | (8x)+(6-x)=34 | | 4(t-3)-3(t-2)=2t+8 | | 2(20+n)=52 | | y+5.3=2.6 | | u+6=15 | | x+2.7=3.1 | | 25y-24y=4+9 | | -24b=672 | | 2(12+x)=52 | | y-12=1 | | 8-(7x)=-29 | | -12=x^2+1 | | -12=x^3+1 | | 2(7-x)=43 |